Sistem Informasi Inventori dan Optimasi Pengiriman Stok Produk Menggunakan Metode Weighted Moving Average - Raymond Sutjiadi; Peter Santoso (SMATIKA JURNAL, 2020)
CV. XYZ is a company founded in 2010 and located in Surabaya, has a business in crispy chicken snack. With the fast growing of its customers and product types, the planning and stock listing of products to be distributed to each stand will become more complicated. On the other side, stock delivery calculation which is done manually based on weekly historical data caused imbalance stock between the supply of raw material in stockroom and demand in each stand. Therefore, in this research is proposed a system of inventory and stock delivery using Weighted Moving Average forecasting method. So that stock delivery will be more efficient.